Pemberdayaan Masyarakat dalam Pengembangan Usaha Mikro Makanan Pendap Kelurahan Rawamakmur Kota Bengkulu - Nola Windirah; Edi Susanto; Lathifah Khairani (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Situation analysis of pendap businesses in Rawamkmur Permai in Bengkulu City shows good prospects in terms of material availability and market targets. However, there are several problems in the business, namely related to the quality and quantity of products in terms of durability, production quantities, and unattractive packaging. Apart from that, there is still a lack of knowledge regarding the legality of digital business and marketing. The main aim of this activity is to improve the quality and quantity of local micro small and medium enterprises in terms of production, packaging, marketing, and licensing. The method used is a training assistance method with simulation techniques. The target of the activity is the family welfare development group in Rawamakmur Permai in Bengkulu City. The stages of service activities consist of: 1) the observation stage (2) mentoring/training stage, (3) the monitoring stage. The result of this activity is an increase in target knowledge regarding the quality and quantity of pendap production. This activity also produces pendap products that have longer shelf life and attractive packaging.